ISLAMIC REAL ESTATE INVESTMENT TRUSTS (I-REITS): FRAMEWORK AND ITS APPLICATIONS IN MALAYSIA - Bin Mohammad, Che Adenan; Borham, Abd. Shakor Bin; Mustapha, Ahmad Sharifuddin; Binti Zainol, Nur Zainatul Nadra; Muhammed, Nik Kamal Wan (International Journal of Psychosocial Rehabilitation, 2020)
Confusion still exists, particularly among our society in Malaysia on Islamic Real Estate Investment Trust (iREITS), especially in terms of definition as one of investment instrument in the Islamic capital markets, its transaction and its application process, as well as its relationship with conventional unit trust. This confusion is caused by having no exposure to the concept of (iREITS), in addition to the dominance of the theory and concept of conventional unit trust and its influence in the practice of real estate investment unit trust particularly in Malaysia, or the world at large. As a result, this type of investment unit trust is less known among investors and the Muslim community itself. Even in investment transactions, they usually prefer other products of property unit trust from a conventional unit trust system, while Islamic Real Estate Investment Trust itself was introduced in the Islamic financial markets. Thus, this article aims to dispel some of the confusion and ignorance of it and try to show the essence of Islamic unit trust property, its transaction and applications processing, the distribution, the approach and the multiple dimensions of Islam in highlighting it as an investment instrument in Islamic Muamalat system. Consequently, this is to show the contribution of this investment product (iREITS) as an alternative to Islamic investors to expand their financial and property in the Islamic capital market in Malaysia and the world.